If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(g + -2) + -4 = 2(g + 3) Reorder the terms: 2(-2 + g) + -4 = 2(g + 3) (-2 * 2 + g * 2) + -4 = 2(g + 3) (-4 + 2g) + -4 = 2(g + 3) Reorder the terms: -4 + -4 + 2g = 2(g + 3) Combine like terms: -4 + -4 = -8 -8 + 2g = 2(g + 3) Reorder the terms: -8 + 2g = 2(3 + g) -8 + 2g = (3 * 2 + g * 2) -8 + 2g = (6 + 2g) Add '-2g' to each side of the equation. -8 + 2g + -2g = 6 + 2g + -2g Combine like terms: 2g + -2g = 0 -8 + 0 = 6 + 2g + -2g -8 = 6 + 2g + -2g Combine like terms: 2g + -2g = 0 -8 = 6 + 0 -8 = 6 Solving -8 = 6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| (1+7)-(5+3)= | | 3a+a+2-2a-1=3a+6 | | 4m+11m-7=8 | | x-18=-18 | | 6x-2(x+4)=8(x-2)+6 | | 2y-5=40 | | 60x^3-24x-3x=0 | | m-6=7 | | (7x+4)(2x-5x-3)=0 | | 69+1x=69+1x | | 2y-5= | | 4+6b=8(4b-6) | | 69+1=69+1x | | 1.5x-7=0.5 | | 5x-5=-45 | | 3x+x+10=16 | | 0.28-0.02(x+3)=-0.03(1-x) | | y=3(x-2)+x | | -(3y+4)-(-2y-5)=-1 | | 4(2n+5)=8(9n+3)+6 | | 28x+25=4(6x+5)+4x+5 | | 32=-8+4x | | 6(n+3)=12-12n | | 5+5x=9+2x | | x=-2y^2+12y-15 | | 2.5x+7.5=20 | | 4x=2x+2 | | x+31=3x+11 | | 16=-3(2x+3)+7x | | Y=x^3-2 | | 38-3x=52+x | | -8+10x=102 |